Mapjack: A Mobile Wiki for Collaborative Map Making - Ntabathia, Jude (Proceedings of the AAAI Conference on Human Computation and Crowdsourcing, 2014)
Volunteered geographic information has introduced new forms of user generated content. Sadly, the generation of such content is not inclusive. There is need to improve not only tools but also social processes to bring about more inclusivity in participation.